2017
DOI: 10.1161/hypertensionaha.117.07802
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Inflammation, and Vascular Aging in Hypertension

Abstract: Figure.Central role of oxidative stress in accelerated vascular aging in hypertension. AT1R indicates angiotensin II receptor type 1; BH 2 , dihydrobiopterin; BH 4 , tetrahydrobiopterin; BMP, bone morphogenic protein; CypD, cyclophilin D; eNOS, endothelial NO synthase; ET1R, endothelin 1 receptor; H 2 O 2 , hydrogen peroxide; MMP, matrix metalloproteinase; Nox, NADPH oxidase; O 2 −. , superoxide anion; RANTES, regulated on activation, normal T cell expressed and secreted chemokine; and SmgGDS, GTP-binding prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
343
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 554 publications
(365 citation statements)
references
References 102 publications
14
343
0
8
Order By: Relevance
“…Many of the features described in the EC-KO mice including vascular dysfunction, arterial remodeling, aortic stiffness, and aging are typically associated with oxidative stress and increased activation of Noxs as demonstrated in various models of CVD [42]. Our findings here of increased NADPH-mediated O 2 − production support this notion and suggest that EC Nox activity may be increased in EC-KO mice.…”
Section: Discussionsupporting
confidence: 78%
“…Many of the features described in the EC-KO mice including vascular dysfunction, arterial remodeling, aortic stiffness, and aging are typically associated with oxidative stress and increased activation of Noxs as demonstrated in various models of CVD [42]. Our findings here of increased NADPH-mediated O 2 − production support this notion and suggest that EC Nox activity may be increased in EC-KO mice.…”
Section: Discussionsupporting
confidence: 78%
“…The first principal component was mainly contributed to by parameters that are typically aberrant in clinical cases of placenta‐mediated hypertension, including peripheral resistance, endoglin, cardiac output, and PlGF 12, 13. Conversely, the main contributors to the second and third principal components align with pathways to hypertension relating to maternal clinical characteristics and systemic inflammation, respectively 14, 15. These findings highlight the critical need for the development of pathway‐specific antihypertensive treatment strategies, with the understanding that hypertension in pregnancy does not involve only one common origin 7…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is a complex group of clinical syndromes. Although the specific mechanisms remain unclear, it has been demonstrated that a variety of pathological factors are involved in the process of hypertension, among which immune responses and inflammation are most closely related to hypertension (Kirabo et al, 2014;Pober, 2014;Guzik and Touyz, 2017).…”
Section: Interleukin-12 Family Members and Hypertensionmentioning
confidence: 99%